Effect of Cannabis Use on Human Immunodeficiency Virus DNA During Suppressive Antiretroviral Therapy. (10th May 2019) - Chaillon, Antoine; Nakazawa, Masato; Anderson, Christy; Christensen-Quick, Aaron; Ellis, Ronald J; Franklin, Donald; Morris, Sheldon R; Gianella, Sara
Abstract: Cannabis use is frequent among people living with human immunodeficiency virus (HIV) and is associated with reduced systemic inflammation. We observed a faster HIV DNA decay during antiretroviral therapy among cannabis users, compared to those with no drug use. No cannabis effect was observed on cellular HIV RNA transcription.